Beltraneja y Francisco Pacheco: nuevo apógrafo de un cuestionado poema satírico - Almanza, Carla (2009)
The purpose of this article is to give notice of a new copy or apograph of the epic-satirical poem Beltraneja. The peculiarity of this copy lies in the fact that it is part of a seventeenth-century codex made by the Sevillian painter Francisco Pacheco. Through the analysis of this document, not only do we try to construct a critical view of the studies on the poem developed so far, but we also propose a series of reflections around the anonymity and the date of the poem starting from Pacheco’s cultural context. Beyond pretending to precise paratextual and ideological interpretation issues, this piece of work aims to enhance the historical and literary significance of a representative product of the colonial Spanish-American satire.